Credit information in universal banking: A clinical study - Hans-Peter Burghof; Claudia Henschel (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
We studied information and interaction processes in six lending relationships between a universal bank and medium sized firms. The study is based on the credit files of the respective firms. If no problems occur in these lending relationships, bank monitoring is based mainly on cheap, retrospective and internal data. In case of distress, more expensive, prospective and external information is used. The level of monitoring and the willingness to renegotiate the lending relationship depends on what the lending officers can learn about the future prospects of the firm from the behaviour of the debtors. We identify both signalling and bonding activities. Such learning from past behaviour seems to allow monitoring at low cost, whereas the direct observation of the firm's investment outlook seems to be very costly. Also, too much knowledge about the firm's investments might leave the bank in a very strong bargaining position and distort investment incentives. Therefore, the traditional view of credit assessment as observation of the quality of a borrower's investment programme needs to be reconsidered.
urn:nbn:de:hebis:30-9510
Keywords: G21; G32; G33; 330; banking; relationship lending; renegotiation; distress